Undertaking general practice quality improvement to improve cancer screening - a thematic analysis of provider experiences - Steven A. Trankle (BMC, 2021)
Abstract Background Cancer is a major cause of illness and death, and its incidence and mortality can be reduced through effective screening. In order to improve below target screening rates in one region of Australia, the local Primary Health Network supported local general practices to implement a range of quality improvement initiatives. Methods We used a qualitative approach and interviewed 18 general practice staff and five Primary Health Network staff and contractors to understand their experiences with these quality improvement initiatives. Results In a thematic analysis, we identified four key themes related to program set-up and implementation; patient and community education and promotion; engaging patients and communities in screening; and general practice enhancement. Program roles were clear and understood, and the program received strong oversight and support. Practice staff felt supported and motivated. Information Technology was a challenge for many practices often requiring tailored assistance. Education provided by practices facilitated patient empowerment but practice staff noted difficulties engaging patients in screening. Practices were enhanced though strong leadership and teamwork and practice learning activities. Conclusions The tailored evidence-based quality improvement initiatives were considered effective in supporting general practices to increase their cancer screening. Key facilitators reported by participants included use of Plan-Do-Study-Act cycles, enhanced data entry and audit capacity, effective recall and reminder systems and maintaining staff motivation.